Mendeteksi Fraud di Era Digital: Pengaruh Literasi Akuntansi terhadap Kesiapan UMKM dalam Mengadopsi AI: Detecting Fraud in the Digital Era: The Impact of Accounting Literacy on MSME Readiness to Adopt AI - Hani Fitria Rahmani; Ricky Bryan D.P. Tampubolon; Irma Sriwijayanti; Iman Firmansyah (JRAK: Journal of Accounting Research and Computerized Accounting, 2025)
The digital transformation driven by Artificial Intelligence (AI) has become a strategic necessity for fraud detection, including within the Micro, Small, and Medium Enterprises (MSMEs) sector. This study aims to analyze the effect of accounting literacy on the readiness to implement AI-based fraud detection systems, and to examine the mediating role of fraud risk awareness. A quantitative approach was employed, using a survey of 120 MSME actors in the Jabodetabek area, and data were analyzed through Structural Equation Modeling–Partial Least Squares (SEM-PLS). The results reveal that accounting literacy has a positive and significant effect on AI readiness. Furthermore, fraud risk awareness significantly mediates this relationship. These findings reinforce the framework of the Theory of Planned Behavior, where accounting literacy shapes attitude and perceived behavioral control, while fraud awareness serves as a subjective norm that supports technology adoption. The study concludes that strengthening internal capacity is a crucial foundation for effective and sustainable digital transformation in MSMEs.